A Delphi survey and international e-survey evaluating the Doha agreement meeting classification system in groin pain: Where are we 5 years later?. Issue 1 (January 2022) - Heijboer, Willem M.P.; Weir, Adam; Delahunt, Eamonn; Hölmich, Per; Schache, Anthony G.; Tol, Johannes L.; de Vos, Robert-Jan; Vuckovic, Zarko; Serner, Andreas
Abstract: Objectives: To evaluate the adoption of and opinions on the Doha agreement meeting classification in groin pain in athletes. Design: Delphi survey and e-survey. Methods: A 2-round Delphi survey among the Doha agreement meeting expert group, and a separate international e-survey among clinicians who regularly assess athletes with groin pain. Clinical cases were presented, and participants provided their preferred terms for the diagnoses. All participants reported if they had adopted the Doha agreement meeting classification system in their practice. The Doha agreement meeting experts also shared opinions on amendments to the classification system, and reported their level of agreement with suggested statements. Results: In the Delphi survey, the Doha agreement meeting experts ( n  = 21) reported 8–11 different terms for their primary diagnosis of each presented case. The Doha agreement meeting terminology was used by 50–67% of these experts. In the international e-survey ( n  = 51), 12–15 different diagnostic terms were reported in each clinical case, and 43–55% of clinicians used the Doha agreement meeting terminology. Adoption of the Doha agreement classification system in practice was reported by 73–82% of the Doha agreement meeting experts and 57–69% of the clinicians in the international e-survey. The experts suggested 49 statements regarding amendments to the classification system. Seven of these reached >75% agreement or disagreement. Conclusions: Five years after publication, the majority of the Doha agreement expert group and independent international clinicians report adopting the Doha agreement meeting classification system. There is still considerable heterogeneity in diagnostic terminology when clinical cases are presented, and disagreement on statements related to amendments of the current classification system.